2013
DOI: 10.1080/00103624.2013.748064
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cost Analysis of Organic and Conventional Farming in Hungary

Abstract: The cost-profit relations of organic and conventional farming were examined using natural and financial data of a large agricultural company in western Hungary and economic models characterizing private farms in eastern Hungary. The differences in cost structures reflect variable conditions relating to certain crops but they can be well explained by the differences in the technologies used. According to the production data, direct costs per hectare in organic farming were less in all of the four examined crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…This also raises the question of the recent whole farm profitability of breeding suckler cows under Common Agricultural Policy schemes. The findings concerning organic and conventional cattle breeding are in accordance with other authors (Delate et al, 2003;Pimentel et al, 2005;Urfi et al, 2013;Gillespie and Nehring, 2013). At the same time, studies point out that the extra price for organic products is often insufficient to achieve greater profits every year.…”
Section: Resultssupporting
confidence: 87%
“…This also raises the question of the recent whole farm profitability of breeding suckler cows under Common Agricultural Policy schemes. The findings concerning organic and conventional cattle breeding are in accordance with other authors (Delate et al, 2003;Pimentel et al, 2005;Urfi et al, 2013;Gillespie and Nehring, 2013). At the same time, studies point out that the extra price for organic products is often insufficient to achieve greater profits every year.…”
Section: Resultssupporting
confidence: 87%
“…Adhikari (2009) also concluded that carrot production in organic system was insignificantly lower than inorganic system, moreover, revenue per hectare for carrot production remained lower in organic system relative to inorganic system whilst, in contrast, gross margin was found higher in organic production system as compared to inorganic production system. Urfi et al (2013) found that per hectare cost of organic farming was lower than that of conventional farming for crops such as grape, wheat, sunflower, maize, the lower cost of organic farming was due to lower costs of plant protection and fertilization. Furthermore, it also concluded that organic farming was more profitable.…”
Section: Gross Margin Of Conventional-inorganic and Sri-organic Plantmentioning
confidence: 99%
“…In most of the study, it is found that organic farming is a sustainable farming practice as yield and net profit are higher in comparison with conventional farming, and proper technical guidance, quality of bio inputs at an affordable price and forward linkage will increase agricultural productivity and improve farmer’s livelihood (Reddy and Mundinamani, 2013; Poyyamoli and Padmavathy, 2011). However, it was found that the yield in organic crop production is low as compared to conventional farming; however, the cost per hectare selling price was greater (Urfi et al , 2013).…”
Section: Review Of Literaturementioning
confidence: 99%